A CASE OF INTRAMURAL CYST OF THE COMMON BILE DUCT - ABE, Hideo; KANEKO, Jyuro; FUKUZAWA, Masahiro; IKEDA, Taro; USUI, Ryohei; PARK, Young J (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2000)
A 37-year-old female was shown by ultrasound at the Medical Examination Center of our hospital to have dilatation of the bile duct. She underwent various tests, including ERCP. As these results suggested a benign cystic tumor of the common bile duct, she underwent cholecystectomy and choledochocystectomy with T-tube drainage. Histopathological examination revealed a true cyst emanating from simple columnar epithelium, but no malignancies. The postoperative course was uneventful, and the patient was discharged one month after surgery. To date, there have been no signs of recurrence. Including autopsied cases, there have been only eight reported cases of this disease in the Japanese literature.